Oczne czynniki ryzyka zwyrodnienia plamki związanego z wiekiem (AMD). Część II - Drobek-Słowik, Monika; Karczewicz, Danuta; Safranow, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the relationship between different ocular factors and age-related macular degeneration (AMD). Material and methods: 281 eyes with AMD diagnosed with fundus fluorescein angiography were included to the study and divided into two groups: with dry and exudative type of AMD. 149 eyes without AMD consisted of control group. We performed ophthalmic examination and questionnaire. We collected data concerning exposition to the sun, using of sunglasses and other factors. Results: Arterial sclerosis in the retina was associated with twice 2-fold increased risk (OR = 1.96) of exudative AMD.There was not association of iris color, using of sunglasses, work conditions and age-related macular degeneration. Conclusions: The coexistance of arterial sclerosis in the retina suggests that vascular disorders take part in pathogenesis of exudative type of AMD. Factors like iris color, using of sunglasses and work are not associated with the risk of AMD.